Assessing the progress of river restoration in the UK: has biophysical condition improved over two decades of intervention? - Moore, Harriet Elizabeth; Mercer, Theresa G.; de Alwis Pitts, Dilkushi; Beagley, Sam; Naura, Marc; Bryden, Alexandra (Wiley, 2021)
Biophysical condition is one indicator of the immediate success of efforts to restore degraded rivers as well as longer-term progress towards improving water quality. In the context of the Water Framework Directive (WFD), the biophysical condition of river systems in the UK also reflects how well international environmental policy translates into improved river management domestically. We assess whether the condition of river systems in the UK has improved or declined over the past two decades, whether regions identified by the first WFD assessment have improved or declined, and thus, how effectively international policy has been implemented nationally. Methods include: statistical and spatial analysis of more than 25,000 habitat condition records collated in the River Habitat Survey over the 1990s and 2000s; computing of an Index of Change for Local Authorities; and comparison of Indices of Change with a sub-sample of 1,727 WFD assessments conducted in 258 Local Authorities. Findings include that three of four measures indicate that biophysical quality has declined, although only the decline in one measure (habitat quality) was statistically significant. Riparian quality has improved, although measures do not consider invasive compared to native coverage. In total, 27 regions were identified with the worst declining quality. Comparative analysis of regions suggests that condition has declined most substantially in regions that were previously in “good” condition. Priorities for future investment include improving degraded sites, protecting high quality sites, and increasing monitoring of “data poor” regions. Our methodology offers an approach for utilising “messy” routinely collated data like the RHS. However, guidelines are needed to support the use of similar datasets for the international river restoration community.
Keywords: Habitat condition; observational data; Water Framework Directive; River Restoration; monitoring and assessment